Treatment of advanced thyroid cancer with targeted therapies: ten years of experience. Issue 4 (April 2016) - Viola, David; Valerio, Laura; Molinaro, Eleonora; Agate, Laura; Bottici, Valeria; Biagini, Agnese; Lorusso, Loredana; Cappagli, Virginia; Pieruzzi, Letizia; Giani, Carlotta; Sabini, Elena; Passannati, Paolo; et al.
Abstract: Thyroid cancer is rare, but it is the most frequent endocrine malignancy. Its prognosis is generally favorable, especially in cases of well-differentiated thyroid cancers (DTCs), such as papillary and follicular cancers, which have survival rates of approximately 95% at 40 years. However, 15–20% of cases became radioiodine refractory (RAI-R), and until now, no other treatments have been effective. The same problems are found in cases of poorly differentiated (PDTC) and anaplastic (ATC) thyroid cancers and in at least 30% of medullary thyroid cancer (MTC) cases, which are very aggressive and not sensitive to radioiodine. Tyrosine kinase inhibitors (TKIs) represent a new approach to the treatment of advanced cases of RAI-R DTC, MTC, PDTC, and, possibly, ATC. In the past 10 years, several TKIs have been tested for the treatment of advanced, progressive, and RAI-R thyroid tumors, and some of them have been recently approved for use in clinical practice: sorafenib and lenvatinib for DTC and PDTC and vandetanib and cabozantinib for MTC. The objective of this review is to present the current status of the treatment of advanced thyroid cancer with the use of innovative targeted therapies by describing both the benefits and the limits of their use based on the experiences reported so far. A comprehensive analysis and description of the molecular basis of these therapies, as well as new therapeutic perspectives, are reported. Some practical suggestions are given for both the choice of patients to be treated and their management, with particular regard to the potential side effects.